A Antroponomástica Comparada - Márcia Sipavicius Seide (Onomástica desde América Latina, 2020)
The emergence of onomastic studies in Europe dates to the 19th century when language studies were made according to the approaches of Philology and Comparative Grammar. The interest in comparing anthroponymies of different languages and/or cultures, however, is and even more more recent the perception that studies of this nature form a specific subarea that I call Comparative Anthroponomastics. In this work, I elucidate how this subarea is configured from theoretical, epistemological pragmatical and applied points of view. To this purpose, I present results of bibliographic research based on 16 complete papers published in international congresses of Onomastics from 2011 to 2018 and 06 researchers conducted by me and/or colleagues in this area totaling 22 studies.